Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Here is the initial term and recursive formula for a sequence:

[tex]\[
\begin{array}{l}
f(1) = 40 \\
f(n) = -f(n-1)
\end{array}
\][/tex]

Which explicit formula can be used to define this sequence?

[tex]\[
\begin{array}{cc}
A. \, f(n) = -39^{n-1} & C. \, f(n) = 39 \\
B. \, f(n) = 40 & D. \, f(n) = 40(-1)^{n-1}
\end{array}
\][/tex]


Sagot :

Let's determine the explicit formula for the given sequence step-by-step.

The sequence is initially defined as follows:
[tex]\[ f(1) = 40 \][/tex]
[tex]\[ f(n) = -f(n - 1) \][/tex]

To understand the pattern in the sequence, let's evaluate the first few terms:

1. For [tex]\( n = 1 \)[/tex]:
[tex]\[ f(1) = 40 \][/tex]

2. For [tex]\( n = 2 \)[/tex]:
[tex]\[ f(2) = -f(1) = -40 \][/tex]

3. For [tex]\( n = 3 \)[/tex]:
[tex]\[ f(3) = -f(2) = -(-40) = 40 \][/tex]

4. For [tex]\( n = 4 \)[/tex]:
[tex]\[ f(4) = -f(3) = -40 \][/tex]

5. For [tex]\( n = 5 \)[/tex]:
[tex]\[ f(5) = -f(4) = -(-40) = 40 \][/tex]

From these calculations, it's clear that the sequence alternates between [tex]\( 40 \)[/tex] and [tex]\( -40 \)[/tex].

Let's identify the pattern:

- When [tex]\( n \)[/tex] is odd (1, 3, 5,...), [tex]\( f(n) \)[/tex] is [tex]\( 40 \)[/tex].
- When [tex]\( n \)[/tex] is even (2, 4, 6,...), [tex]\( f(n) \)[/tex] is [tex]\( -40 \)[/tex].

This alternating sign can be expressed using the term [tex]\((-1)^{n - 1}\)[/tex]:

- For [tex]\( n = 1 \)[/tex], [tex]\( (-1)^{1-1} = (-1)^0 = 1 \)[/tex]
- For [tex]\( n = 2 \)[/tex], [tex]\( (-1)^{2-1} = (-1)^1 = -1 \)[/tex]
- For [tex]\( n = 3 \)[/tex], [tex]\( (-1)^{3-1} = (-1)^2 = 1 \)[/tex]
- For [tex]\( n = 4 \)[/tex], [tex]\( (-1)^{4-1} = (-1)^3 = -1 \)[/tex]

Hence, the explicit formula is:
[tex]\[ f(n) = 40 \cdot (-1)^{n - 1} \][/tex]

Among the given options, the correct explicit formula that matches our derivation is:
[tex]\[ f(n) = 40 \cdot (-1)^{n - 1} \][/tex]

Thus, the explicit formula used to define this sequence is:
[tex]\[ f(n) = 40 \cdot (-1)^{n - 1} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.